THE EDUCATIONAL VALUE AND TEACHING STRATEGY IN “FREEDOM WRITER” BY RICHARD LAGRAVENESE - Ayu Kartika Listiyana; Rifari Baron (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: This research aims to analyze the educational value and teaching strategy in the “Freedom Writer” film by Richard Lagravenese. Based on the theories of educational value and teaching strategies, there are four primary points to analyze: 1) How is Educational Value in ‘Freedom Writer Film’ by Richard Lagravenese? 2) What are the Teaching Strategies in ‘Freedom Writer Film’ by Richard Lagravenese? 3) There are eleven kinds of educational value that appear in “Freedom Writer” by Richard Lagravenese based on Linda, they are honesty, courage, peace-ability, self-reliance and potential, self-discipline and moderation, loyalty and dependability, respect, unselfishness, and sensitivity, kindness & friendliness, justice and mercy, and love. 4) There are five kinds of teaching strategies that appear in Richard Lagravenese based on Brown; they are content-based instruction, theme-based instruction, experiential learning, episode hypothesis, and task-based teaching.Keywords: educational value, teaching strategy, film.